Visual Servoing Tracking Control of a Ball and Plate System: Design, Implementation and Experimental Validation. (9th July 2013) - Ho, Ming-Tzu; Rizal, Yusie; Chu, Li-Ming
This paper presents the design, implementation and validation of real-time visual servoing tracking control for a ball and plate system. The position of the ball is measured with a machine vision system. The image processing algorithms of the machine vision system are pipelined and implemented on a field programmable gate array (FPGA) device to meet real-time constraints. A detailed dynamic model of the system is derived for the simulation study. By neglecting the high-order coupling terms, the ball and plate system model is simplified into two decoupled ball and beam systems, and an approximate input-output feedback linearization approach is then used to design the controller for trajectory tracking. The designed control law is implemented on a digital signal processor (DSP). The validity of the performance of the developed control system is investigated through simulation and experimental studies. Experimental results show that the designed system functions well with reasonable agreement with simulations.